What if public-private alliances are strengthened? Rice research and scaling-up in Ecuador - Andrade, R.; Buritica, A.; Marin, D. (2023)
The impact of the Ecuador government's KIT program was distinctly positive in encouraging the adoption of improved crop varieties. This positive effect was particularly concentrated within the specific varieties actively promoted by the agricultural industry. However, it's worth noting that this effect is primarily concentrated among larger rice producers. In our descriptive analysis, we observe that producers who embrace improved varieties tend to experience an increase in their costs, although this increase is not statistically significant. This observation may provide insights into why smaller producers are less inclined to adopt such varieties. The impact of the KIT program does not manifest as significant increases in rice producers' average yield per hectare. This underscores the importance of not just providing inputs but also offering the necessary technical assistance to ensure that improved varieties are effectively utilized.